Stock Risk Management Mitigation Strategy in the Transfer of Petroleum Work Management in Indonesia - Suharno, FA Suharno; Rozikin, Imam; Felina, Felina (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
This research aims to understand stock management, namely optimizing the combination of quality of goods, costs, and time, in this case, the availability of goods. House of Risk model risk management. Analyze and select a sequence of risks and determine mitigation strategies. The research method uses a qualitative approach that describes objective conditions in the field. Data collection techniques include interviews, observation, and documentation studies. Conclusion The analysis is used as a basis for the stock management mitigation strategy that will be taken. Determination of mitigation priorities is carried out to manage the allocation of required resources and control the emergence of risks. If existing mitigation efforts cannot solve the existing problem, the new company must change its mitigation strategy. A total of 34 risk events and 35 risk agents were identified when observing business processes. HOR-1 and the Pareto approach have been proven to be used to determine which risk agents should be prioritized for handling. Preventive actions are identified to reduce the negative impact of existing risks. HOR-2 succeeded in determining the ranking of preventive actions to be used to determine the mitigation strategy to be chosen.